African alternatives - Chabal, Patrick, 1951-2014; Engel, Ulf; Haan, Leo de, editor (African-Europe Group for Interdisciplinary Studies (Series) ;, 2007)
To stimulate the exploration of African initiative and creativity beyond immediate socio-economic and political circumstances, this book demonstrates that societies in Africa have always showed the ability to negotiate whatever constraining ecological, economic and political circumstances they faced.